Magnetotransport properties of 8-Pmmn borophene: effects of Hall field and strain. (12th June 2018) - Islam, SK Firoz
Abstract: The polymorph of 8-Pmmn borophene is an anisotropic Dirac material with tilted Dirac cones at two valleys. The tilting of the Dirac cones at two valleys are in opposite directions, which manifests itself via the valley dependent Landau levels in presence of an in-plane electric field (Hall field). The valley dependent Landau levels cause valley polarized magnetotransport properties in presence of the Hall field, which is in contrast to the monolayer graphene with isotropic non-tilted Dirac cones. The longitudinal conductivity and Hall conductivity are evaluated by using linear response theory in low temperature regime. An analytical approximate form of the longitudinal conductivity is also obtained. It is observed that the tilting of the Dirac cones amplifies the frequency of the longitudinal conductivity oscillation (Shubnikov–de Haas). On the other hand, the Hall conductivity exhibits graphene-like plateaus except the appearance of valley dependent steps which are purely attributed to the Hall field induced lifting of the valley degeneracy in the Landau levels. Finally we look into the different cases when the Hall field is applied to the strained borophene and find that valley dependency is fully dominated by strain rather than Hall field. Another noticeable point is that if the real magnetic field is replaced by the strain induced pseudo magnetic field then the electric field looses its ability to cause valley polarized transport.